A Numerical Simulation for Darcy-Forchheimer Flow of Nanofluid by a Rotating Disk With Partial Slip Effects - Ullah, Malik Zaka; Serra-Capizzano, Stefano; Baleanu, Dumitru (Frontiers in Physics, 2020)
This communication examines Darcy-Forchheimer 3D nanoliquid flow by a rotating disk with heat generation/absorption. Impacts of Brownian movement and thermophoretic are considered. Velocity, concentration and temperature slips at surface of rotating disk are utilized. The change from the nonlinear partial differential framework to the nonlinear ordinary differential framework is assumed into position by utilizing appropriate variables. Shooting technique is utilized to develop numerical solution of resulting framework. Graphs have been sketched just to examine that how concentration and temperature fields are affected by several pertinent flow parameters. Skin frictions and local Sherwood and Nusselt numbers are additionally plotted and analyzed. Furthermore, the concentration and temperature fields are enhanced for larger values of thermophoresis parameter.